Analysis and Design of MSMEs Support System Based on Information Technology (Analisis dan Perancangan Sistem Pendukung UMKM Berbasis Teknologi Informasi) - Rintho Rante Rerung (BBPSDMP KOMINFO MAKASSAR, 2018)
The role of MSMEs in Indonesia’s economy is undeniable because it is able to survive and be an economic turbine. History has proved that the type of business that can survive the economic crisis in Indonesia is MSMEs. However, MSMEs in Indonesia is considered to have low competitiveness in internal factors such as production and processing, marketing, human resources, design, and technology. High competitiveness is needed to compete in global markets such as the ASEAN Economic Community competitiveness in internal factors such as production and processing, marketing, human resources, design, and technology. High competitiveness is needed to compete in global markets such as the ASEAN Economic Community. This condition is challenging yet give opportunities to MSMEs. Therefore, implementing information technology is a solution to increase competitiveness. Although the device of information technology is getting cheaper and more affordable, most MSMEs still consider it expensive due to financial limitations and lack of expertise in using the computer. In consequence, support from various parties, not only the government but also groups such as academics, practitioners, and college students, is significantly needed. Thus, it is necessary to create the MSME Support System as a medium of information for the MSMEs' agents with potential supporters who are academics, practitioners, and college students.Peran UMKM dalam perekonomian Indonesia memang tidak diragukan lagi karena terbukti mampu bertahan dan menjadi roda penggerak ekonomi. Sejarah telah membuktikan, ketika Indonesia mengalami krisis ekonomi, bentuk usaha yang bisa bertahan adalah UMKM. Akan tetapi, UMKM di Indonesia dinilai masih belum memiliki daya saing yang tinggi, dalam dari faktor internal seperti produksi dan pengolahan, pemasaran, sumber daya manusia, desain dan teknologi. Daya saing yang tinggi sangat diperlukan dalam bersaing dengan pasar global seperti Masyarakat Ekonomi Asean. Kondisi ini memang memberikan tantangan, namun juga dapat memperoleh peluang bagi UMKM. Mengadopsi penggunaan teknologi informasi merupakan salah satu solusi untuk meningkatkan daya saing. Meskipun perangkat teknologi informasi semakin murah dan terjangkau, namun untuk sebagian besar UMKM masih merupakan barang mahal karena keterbatasan finansial dan kurangnya keahlian dalam menggunakan komputer sendiri. Dengan kondisi ini tentu sangat diperlukan dukungan dari berbagai pihak, tidak hanya pemerintah, namun semua kalangan seperti kalangan akademisi, kalangan praktisi dan kalangan mahasiswa. Oleh sebab itu membangun Sistem Pendukung UMKM sebagai media informasi bagi para pelaku UMKM dengan para calon supporter yang terdiri dari kalangan akademisi, kalangan praktisi dan kalangan mahasiswa sangat diperlukan.